The place of deportation of the Babylonian divine statues - Villard, Pierre (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2023)
After winning the civil war that followed the murder of Sennacherib and ascending to the throne, Esarhaddon compiled collections of prophecies that justified his rise to power. These collections, transposed into literary language and organised in sections, each corresponding to what a prophet or prophetess had proclaimed, were probably read during politico-religious ceremonies (Parpola 1997: lxviii–lxx).